Thermodynamic and kinetics analysis of the sulfur-fixed roasting of antimony sulfide using ZnO as sulfur-fixing agent - Ouyang Z.; Chen Y.F.; Tian S.Y.; Xiao L.; Tang C.B.; Hu Y.J.; Xia Z.M.; Chen Y.M.; Ye L.G. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2018)
Currently, the commercial antimony metallurgy is mainly based on pyrometallurgical processes and oxidative volatilization of Sb2S3 is an essential step. This step includes the problems of high energy consumption and low concentration of SO2 pollution. Aiming at these problems, we present a new method of sulfur-fixing roasting of antimony sulfide. This method uses ZnO as a sulfur-fixing agent, and roasting with Sb2S3 was carried out at 673 K~1073 K to produce Sb2O3 and ZnS. By calculating the thermodynamics of the reactions, we can conclude that the Gibbs Free Energy Change (ΔGθ) of roasting reaction is below -60 kJ/mol and the predominance areas of Sb2O3 and ZnS are wide and right shifting with the temperature increase, which all indicates that this method is theoretically feasible. The reacted products between Sb2S3 and ZnO indicated that the reaction began at 773 K and finished approximately at 973K. We used the Ozawa-Flynn-Wall, Kissinger and Coats-Redfern method to calculate the kinetics of the roasting reaction. The conclusion is as follows: The average values of apparent activation energy (E) and natural logarithmic frequency factor (lnA) calculated by Ozawa-Flynn-Wall, Kissinger and Coats-Redfern were 189.72 kJ·mol-1 and 35.29 s-1, respectively. The mechanism of this reaction was phase boundary reaction model. The kinetic equation is shown as follow, where α represents reaction fraction: 1-(1-α)1/3 = 2.12 x1015 exp(-1.90x105/RT) t.